Questioning of witnesses in order to collect evidence and witness protection in criminal procedure - Lazarov Zorana (Crimen (Beograd), 2018)
A witness is any person who can provide information on a crime committed or a person who committed it which is relevant to establishing the truth. The importance of the testimony of the witness is undoubted, especially in the domain of the fight against organized crime, bearing in mind the fact that it leads to easier detection, proving and suppressing such a phenomenon. The significance is even greater if it is noted that, although unreliable, the witness remains the most important means of proof, and that the testimony of the witness is the evidentiary basis upon which the judgment is based. The evidence credibility can increase by implementing adequate witness protection measures. It can be done by expanding the rights of witnesses, the right to protection first and foremost, with the aim to improve their position in criminal procedure. Expanding the rights of witnesses during criminal procedure, first of all rights to protection, undoubtedly leads to humanization of the criminal law, which will reflect on the improvement of his/her position in the criminal procedure. A witness with a wider scope of protection will provide testimony crucial to solving the criminal case, especially in the prosecution of organized crime. As such, a suspicion is being raised whether the expanding of witness's rights is a consequence of the rise of organized crime in a society which forced the judiciary to react in their struggle against this type of crime. In order for a society to be successful in their struggle against rising organized crime, they must agree to more radical measures which are based on respecting the fundamental legal rules.